Unraveling the local adaptation and population structure of Iberian honey bee - Chávez-Galarza, Julio (2014)
Unraveling the complex evolutionary history of Apis mellifera iberiensis is a challenging task. Several studies have been carried out in the Iberian honey bee to explain its origin, suggesting two possible hypotheses: a primary intergradation process (morphology and allozymes), or a secondary contact process (mtDNA) supported by an abrupt southwestern-northeastern cline formed by two divergent lineages. Surveys with microsatellites support neither hypothesis. The goal of this work is to unravel the evolutionary history of the Iberian honey bee using SNPs. To that end, 711 individuals of A. m. iberiensis were collected in 23 sites across three north-south transepts in the Iberian Peninsula. This collection was genotyped for 1536 SNPs using the GoldenGate assay of Illumina. The SNP dataset was examined in search for signatures of selection by coalescence, Bayesian and spatial analysis. Then, the population structure was inferred by using Bayesian methods and multivariate and spatial analysis. Analysis of selection detected 10 loci exhibiting strong selection signal. Their putative functions were determined using the honey bee genomic resources and mapped to putative genes with diverse biological functions, which included vision, detoxification metabolism, and immunity. On the other hand, the population structure recovers the cline southwestern-northeastern found using mtDNA markers.